1987
DOI: 10.1103/physrevlett.59.1080
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the16O(π+,et al.

Abstract: Results from a coincidence measurement of the 16 0(/r + ,/r + 7r~) reaction at 7^+=280 MeV are reported, the first of this class. The energy-and angular-integrated cross section was found to be 2950 ±450 jub and is compared with theoretical predictions. Low-energy positive-pion intensities are found to be much higher than those yielded by a four-body phase-space calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Because of its scalar character, the detection of these pairs does not seem obvious. An indication might be provided by the recent study of (% 2r [8] where an enhanced cross-section has been found. In any case, reactions with two pions in the exit channel seem to be an appropriate tool.…”
mentioning
confidence: 95%
“…Because of its scalar character, the detection of these pairs does not seem obvious. An indication might be provided by the recent study of (% 2r [8] where an enhanced cross-section has been found. In any case, reactions with two pions in the exit channel seem to be an appropriate tool.…”
mentioning
confidence: 95%
“…This state would behave like a Cooper pair in the medium, with repercussions in several observable magnitudes in nuclear reactions [15]. The possibility that such effects could have already been observed in some unexpected enhancement in the ( ¾ ) reaction in nuclei [16] was also noticed there. More recent experiments where the enhancement is seen in the · channel but not in the · · channel [17] have added more attraction to that conjecture.…”
Section: The Interaction In the Nuclear Medium In The Scalar Sectormentioning
confidence: 83%
“…The property (i) could not be explained in terms of the π + A → π + π − p[A − 1] phase space [1]. Nor was a detailed model of the A(π + , π + π − ) reaction [4] able to reproduce the low-energy pion yield, although it embodied the kinematical limits of the experimental apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…In early experimental works on π2π in nuclei it was observed that (i) pions preferentially populate the low-energy part of the kinetic energy spectra [1,2,3], and (ii) the π + π − invariant mass M A π + π − peaks increasingly toward the 2m π threshold as the nucleus mass number increases [3]. The property (i) could not be explained in terms of the π + A → π + π − p[A − 1] phase space [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation